2014
DOI: 10.3389/fphys.2014.00371
|View full text |Cite
|
Sign up to set email alerts
|

Maturation and beyond: proteins in the developmental continuum from enamel epithelium to junctional epithelium

Abstract: Enamel, covering the surface of teeth, is the hardest substance in mammals. It is designed to last a lifetime in spite of severe environmental challenges. Enamel is formed in a biomineralization process that is essentially divided into secretory and maturation stages. While the molecular events of enamel formation during the secretory stage have been elucidated to some extent, the mechanisms of enamel maturation are less defined, and little is known about the molecules present beyond the maturation stage. Seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 59 publications
(82 reference statements)
0
25
0
Order By: Relevance
“…Then, during the maturation these proteins are removed in a complex process, involving two proteases, MMP-20 and kallikrein-4. The individual roles of these proteins are not fully understood but it is clear that among the enamel proteins amelogenin is present in the largest quantity [9,10]. A number of recent studies revealed that mutations of multiple proteins could cause syndrome-associated and nonsyndromic enamel defects (for review see Refs.…”
Section: Significance Of Intrinsically Disordered Proteins Involved Imentioning
confidence: 99%
“…Then, during the maturation these proteins are removed in a complex process, involving two proteases, MMP-20 and kallikrein-4. The individual roles of these proteins are not fully understood but it is clear that among the enamel proteins amelogenin is present in the largest quantity [9,10]. A number of recent studies revealed that mutations of multiple proteins could cause syndrome-associated and nonsyndromic enamel defects (for review see Refs.…”
Section: Significance Of Intrinsically Disordered Proteins Involved Imentioning
confidence: 99%
“…The protein localizes to the basal lamina between the ameloblasts and the enamel surface [ 16 , 17 ], where it is believed to be involved in the formation of the final, thin, non-prismatic enamel layer [ 18 , 19 ]. In rodents, the two other ASPs, odontogenic ameloblast-associated protein (ODAM) and secretory calcium-binding phosphoprotein proline and glutamine rich 1 (SCPPPQ1) are not EMPs and their role is not well known [ 20 ]. ODAM expression pattern is similar to that of AMTN but SCPPPQ1 is expressed later during the late maturation stage [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cluster also includes the genes encoding enamelin (MIM*606585) and ameloblastin (MIM*601259), mutations in which are already known to cause AI (14,25). Amen encodes a 209 amino-acid protein rich in proline, leucine, threonine, glutamine, and glycine, with an N-terminal signal sequence that, once cleaved, gives rise to a mature 20.4 kDa secreted protein (27,28). AMTN has been shown to be restricted to the basal lamina of maturation stage ameloblasts, the structure that links ameloblasts with the developing enamel (29).…”
Section: Introductionmentioning
confidence: 99%